Pengembangan Permainan Kartu Domino Kimia sebagai Media Pembelajaran pada Materi Sistem Koloid Kelas XI SMA/MA - Riri Wahyuni; Fajriah Azra (Universitas Negeri Padang, 2022)
The chemistry domino card game is one of learning media variations is useful for strengthening colloid system material for students. The purpose of this Research is determine the level of validity based on the function of the media. The type of this research used is Research and Development (R and D) which uses a 4-D development model, that consist of some stages namely the define, design, develop, and disseminate stage. Validation questionnaire were given to UNP chemistry lecturer and chemistry teacher at SMAN 1 Bonjol. The data analysis technique used Aikens V. The result of data analysis showed that the chemical domino card game as a learning media for colloid system material had a validity level of 0,89 with valid criteria. The result showed that the chemical domino card game developed was a valid.